Clinical significance of intratumoral HER2 heterogeneity on trastuzumab efficacy using endoscopic biopsy specimens in patients with advanced HER2 positive gastric cancer - Yagi, Shusuke (Gastric Cancer, 2018)
BACKGROUND: We recently reported the clinical significance of intratumoral HER2 heterogeneity on trastuzumab efficacy using surgical specimens; patients with homogeneously HER2 positive gastric cancer benefitted more from trastuzumab. However, the majority of patients are diagnosed by endoscopic biopsy, and surgical specimens are not available in these patients. The aim of this study is to verify clinical significance of HER2 heterogeneity on trastuzumab efficacy using biopsy specimens. METHODS: Eighty-seven patients, who received trastuzumab-based chemotherapy and whose endoscopic biopsy specimens were available for HER2 assessment, were consecutively enrolled. When all tumor cells in all biopsy specimens overexpressed HER2 protein, it was defined as homogeneously HER2 (homo-HER2) positive group, and the others were defined as heterogeneously HER2 (hetero-HER2) positive group. Progression-free survival (PFS), overall survival (OS) and objective response rate (ORR) were evaluated. RESULTS: Thirty-four patients (39%) were diagnosed as the homo-HER2 group and 53 patients (61%) were the hetero-HER2 group. After the median follow-up period of 17.8 months, the median PFS and OS were 7.6 and 17.8 months, respectively. Significant survival differences were shown between the two groups; the homo-HER2 group showed significantly longer PFS (10.8 vs. 6.1 months, HR 0.469 95% CI 0.29–0.77, p = 0.003) and OS (29.3 vs. 14.4 months, HR 0.352 95% CI 0.20–0.61, p < 0.001). ORR was 68.6% in this cohort. Higher response rate (85.2% vs 58.1%, p = 0.020) and deeper response (− 49.0% vs − 40.0%, p = 0.018) were also found in the homo-HER2 group. CONCLUSIONS: Similar to surgical specimens, we verified clinical significance of HER2 heterogeneity on trastuzumab efficacy using endoscopic biopsy specimens. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10120-018-0887-x) contains supplementary material, which is available to authorized users.